Predictive value of CPS combined with inflammatory markers for pathological remission of locally advanced head and neck squamous cell carcinoma after adjuvant immunochemotherapy - Ning, Yudong; Li, Han; Song, Yixuan; He, Yuqin; Liu, Shaoyan; Liu, Yang (Frontiers in Molecular Biosciences, 2025)
ObjectiveTo explore the predictive value of the combined positive score (CPS) and the neutrophil-to- platelet count ratio (NPR) for surgical pathological remission in patients with locally advanced head and neck squamous cell carcinoma (LAHNSCC) who have undergone neoadjuvant immunotherapy combined with chemotherapy (NICC).MethodPatients with LAHNSCC who underwent NICC and surgery from May 2021 to September 2023 were retrospectively analyzed. CPS, NPR and other clinically relevant parameters were collected, which includes gender, age, tumor types, multiple cancer, differentiation, T staging, N staging, immunotherapy cycles and postoperative pathological remission degree.ResultPatients with a higher CPS were significantly associated with a higher pathological complete response (PCR) of the primary site (PPCR) (P = 0.034) and a higher PCR of the lymph nodes (LPCR) (P = 0.085). Specifically, patients with a CPS of ≥20 demonstrated a higher rate of severe pathologic tumor response (PTR), with values of 80.8% compared to 66.7% and 50%. Notably, even patients with a CPS <1 had a relatively high severe PTR rate of 66.7%. Moreover, patients with NPR <0.024 exhibited a higher severe PTR, regardless of the CPS subgroups (P < 0.05).ConclusionHigher CPS can be considered a good predictor of higher PCR after NICC in patients with LAHNSCC. Patients with CPS <1 can still achieve a higher PTR. Patients with NPR <0.024 can help achieve a higher severe PTR in patients with LAHNSCC regardless of the CPS.CPS combined with NPR may have a better predicted value for surgical PTR of HNSCC after NICC.